Glutamine increases body weight and decreases myocardial damage in Trypanosoma cruzi-infected mice treated with nifurtimox - Marín Tello, Carmen Luisa (2021)
Chagas disease, a parasitic infection caused by the protist Trypanosoma cruzi, affects the poorest populations, living in remote, rural areas and urban slums. Although this drug is effective against Chagas disease it presents a number of serious side effects. In residents of high Andean areas with megacolon it can lead to cardiomyopathies. The aim of this study was to investigate whether dietary supplementation with L-glutamine may alleviate some of these symptoms because of its previously observed anti-inflammatory properties. We studied two groups of T. cruzi-infected mice receiving treatment with nifurtimox. One group was fed the standard diet, while the other group’s diet was supplemented with Glutamine. We found that Glutamine supplementation increases body weight (p<0.001), decreases heart-mass-to-body-mass ratio (p<0.001), and decreases the number of amastigotes present in cardiac tissue. Additionally, histopathological analysis showed less heart tissue damage in the group that received Glutaminne in their diet. Therefore, our findings suggest that Glutamine supplementation improves nifurtimox treatment outcomes of T. cruzi infection.